THE EVALUATION OF ROAD CARGO TRANSPORT TECHNOLOGICAL PROCESS (Perner's Contacts, 2012)
The article defines technological indicators for assessing the technological process of road cargo transport. It states formulas for calculation of these indicators and data sources for the calculation. There are stated expected values or effective ranges for each indicator and measures which should hauler do for achieving them.
Keywords: evaluation, road cargo transport, technology, indicators, data sources for evaluation